2019
DOI: 10.3146/ps18-6.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compost Manure on Soil Microbial Respiration, Plant-Available-Water, Peanut (Arachis hypogaea L.) Yield and Pre-Harvest Aflatoxin Contamination

Abstract: Peanut production in Zambia is often characterized by low yields and high aflatoxin incidence in harvested kernels. Soil amendments such as farmyard manure have shown potential to increase yields and reduce pre-harvest aflatoxin incidence. The aim of the current study was to evaluate the effects of composted cattle manure on soil properties that relate to yield and preharvest aflatoxin contamination of peanut kernels. Research evaluated the effects of composted cattle manure on soil respiration, plant-availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Farmyard manure has been associated with up to 90% reduction of total pre-harvest aflatoxin concentrations in harvested peanuts kernels. Furthermore, Chalwe et al (2019) had previously observed that increasing levels of compost resulted in decreased pre-harvest total aflatoxin concentrations in peanut kernels. Manure application not only improves soil fertility, but also to help in combating aflatoxin threat.…”
Section: Discussionmentioning
confidence: 98%
“…Farmyard manure has been associated with up to 90% reduction of total pre-harvest aflatoxin concentrations in harvested peanuts kernels. Furthermore, Chalwe et al (2019) had previously observed that increasing levels of compost resulted in decreased pre-harvest total aflatoxin concentrations in peanut kernels. Manure application not only improves soil fertility, but also to help in combating aflatoxin threat.…”
Section: Discussionmentioning
confidence: 98%
“…In the field of food science, Bandyopadhyay et al [11] and Ezekiel et al [12] explored the reduction of the effect of aflatoxin intake in humans once it is ingested. Most recent studies have been conducted to explore the effect of the external environment on changes in aflatoxin content in foods [13][14][15]. In addition, some research work has made great progress in the degree and severity of aflatoxin contamination to food and common detection methods in various fields [16][17][18].…”
Section: Related Workmentioning
confidence: 99%
“…The capacity to modify the root attributes, especially root length, by extracting the available of water in deeper soil layers represents an important mechanism to avoid drought and ensure plant survivals (Kambiranda et al, 2011). Adding soil amendments improve peanut yield production, soil moisture retention capacity and soil microbial activity (Chalwe et al, 2019).Water deficit stress at vegetative phase had significant effect on leaf solution and proteins. At the end of cetain phase of stress, water deficiency encourage significant proline production in leaves, while led to significant decrease of chlorophyll.…”
Section: Introductionmentioning
confidence: 99%